Acral amelanotic melanoma - Marina Riedi Guilherme; Bruna Cristina Mendes dos Santos; Osvaldo Szenczuk; Ligia Márcia Mário Martin; Cássio Rafael Moreira (Sociedade Brasileira de Dermatologia (SBD), 2022)
Acral amelanotic melanoma is rare and can mimic many entities, such as eccrine poroma, squamous cell carcinoma, plantar wart, and chronic ulcers. Due to the variety of possible differential diagnoses, it is a challenging and frequently late diagnosis. Dermoscopy features can help in early diagnosis. The dermatologist should keep this diagnosis in mind when faced with a pink, progressively growing, irregularly shaped lesion, mainly if located on the hands and feet.